2022
DOI: 10.1021/acsami.2c09179
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Hybrid Anodes with Enhanced Lithium-Storage Performance Realized by a “Synergistic Effect”

Abstract: Alloying-type anodes including Si- and Sn-based materials are considered the most exploitable anodes for high-performance lithium-ion batteries. However, problems of poor kinetics properties and structural failures such as grain pulverization and coarsening hinder their large-scale application. Herein, SnO2/Si@graphite hybrid anodes, with nano-SnO2 and nano-Si thoroughly mixed with each other and loaded onto graphite flakes, have been prepared by a facile ball milling method. Attributed to the “synergistic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The G and 2D band indicate that the C in the sample has high crystallinity. [22] The SnS 2 content in both samples was further confirmed by thermogravimetric analysis (TGA) (Figure 4f and S4, Supporting Information). The weight loss before 200 °C is related to the evaporation of water in the sample.…”
Section: Resultsmentioning
confidence: 71%
“…The G and 2D band indicate that the C in the sample has high crystallinity. [22] The SnS 2 content in both samples was further confirmed by thermogravimetric analysis (TGA) (Figure 4f and S4, Supporting Information). The weight loss before 200 °C is related to the evaporation of water in the sample.…”
Section: Resultsmentioning
confidence: 71%
“…In the high-resolution TEM (HR-TEM) image (Figure d), the lattice fringe of ∼0.31 nm in the core part is related to the (111) of polysilicon and a lattice spacing of ∼0.34 nm in the shell part corresponds to the (110) of SnO 2 . Also, the amorphous N-doped carbon is between the Si core and the SnO 2 shell. , Accordingly, selective area electron diffraction (SAED) (Figure e) shows three clear diffraction rings of Si@NC@SnO 2 , revealing the crystal faces of Si (111), (220), and (311) . Based on the above analysis, the core–shell Si@NC@SnO 2 is composed of nano-Si completely encapsulated into a hybrid shell of SnO 2 quantum dots and N-doped carbon, with good thermal and mechanical stability.…”
Section: Results and Discussionmentioning
confidence: 84%
“…Also, the amorphous N-doped carbon is between the Si core and the SnO 2 shell. 11,27 Accordingly, selective area electron diffraction (SAED) (Figure 2e) shows three clear diffraction rings of Si@NC@SnO 2 , revealing the crystal faces of Si (111), (220), and (311). 27 Based on the above analysis, the core−shell Si@NC@SnO 2 is composed of nano-Si completely encapsulated into a hybrid shell of SnO 2 quantum dots and N-doped carbon, with good thermal and mechanical stability.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…According to previous studies, nanocomposites incorporated with carbonaceous materials have been confirmed to be effective in enhancing the reversibility and reactivity of battery materials. , These nanocomposites increase the ionic and electronic conductivities, enable them to withstand large strains, and accommodate the volume variations of Li-active materials. , Hence, to enhance and optimize the electrochemical performance of SiSe 2 , a SiSe 2 nanocomposite incorporating amorphous carbon was fabricated by using a simple mechanical BM process. The XRD patterns of the SiSe 2 nanocomposite in Figure S11 reveal largely broadened diffraction peaks, indicating the nanocrystalline nature of the SiSe 2 within the nanocomposite.…”
Section: Resultsmentioning
confidence: 99%